Quantitative anatomy of the primary ossification center in the fetal pubis bone - Baumgart, Mariusz (Surg Radiol Anat, 2019)
PURPOSES: Skeletodysplasiae and hereditary dysostoses constitute a group of over 350 disorders of the skeletal system. Knowledge about development of the pubic primary ossification center may be useful in both determining the fetal stage and maturity, and for detecting congenital disorders. The present study was performed to quantitatively examine the pubic primary ossification center with respect to its linear, planar, and volumetric parameters. MATERIALS AND METHODS: Using methods of computed tomography (CT), digital-image analysis and statistics, the size of the pubic primary ossification center in 33 spontaneously aborted human fetuses (18 males and 15 females) aged 22–30 weeks was studied. RESULTS: With no sex and laterality differences, the best-fit growth dynamics for the pubic primary ossification center was modeled by the following functions: y = − 13.694 + 0.728 × age ± 0.356 for its sagittal diameter, y = − 3.350 + 0.218 × age ± 0.159 for its vertical diameter, y = − 61.415 + 2.828 × age ± 1.519 for its projection surface area, and y = − 65.801 + 3.173 × age ± 2.149 for its volume. CONCLUSIONS: The size of the pubic primary ossification center shows neither sex nor laterality differences. The growth dynamics of the vertical and sagittal diameters, projection surface area, and volume of the pubic ossification centers follow proportionately to fetal age. The obtained numerical findings of the pubic ossification center are considered age-specific reference data with clinical implications in the diagnostics of congenital defects.